2016
DOI: 10.1021/acs.est.6b03688
|View full text |Cite
|
Sign up to set email alerts
|

Tetra- and Hexavalent Uranium Forms Bidentate-Mononuclear Complexes with Particulate Organic Matter in a Naturally Uranium-Enriched Peatland

Abstract: Peatlands frequently serve as efficient biogeochemical traps for U. Mechanisms of U immobilization in these organic matter-dominated environments may encompass the precipitation of U-bearing mineral(oid)s and the complexation of U by a vast range of (in)organic surfaces. The objective of this work was to investigate the spatial distribution and molecular binding mechanisms of U in soils of an alpine minerotrophic peatland (pH 4.7-6.6, E = -127 to 463 mV) using microfocused X-ray fluorescence spectrometry and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
73
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 72 publications
12
73
1
Order By: Relevance
“…S4). The dependence of UO 2+x formation on the initial U concentration (i.e., U:solid ratio) is consistent with adsorption of U(IV) to the solid matrix, which suppresses U 4+ (aq) concentrations, hence UO 2+x precipitation (13). The conclusion that U(IV) adsorption to the sample matrix dominates at 1-and 10-μM U concentrations is supported by our estimation that the concentration of adsorption sites is in great excess of U.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…S4). The dependence of UO 2+x formation on the initial U concentration (i.e., U:solid ratio) is consistent with adsorption of U(IV) to the solid matrix, which suppresses U 4+ (aq) concentrations, hence UO 2+x precipitation (13). The conclusion that U(IV) adsorption to the sample matrix dominates at 1-and 10-μM U concentrations is supported by our estimation that the concentration of adsorption sites is in great excess of U.…”
Section: Resultssupporting
confidence: 56%
“…For many years researchers assumed that sparingly soluble minerals, such as UO 2+x , controlled the aqueous concentration of U(IV) and mediated the oxidation of U(IV) to U(VI) under anoxic conditions (5,6). In fact, many researchers have shown that UO 2+x either is not observed in sediments, or is a minor phase (7)(8)(9)(10)(11)(12)(13). The chemical reactivity of U(IV) is controlled by its speciation; for instance, researchers have noted that some biogenically produced forms of U(IV), termed "noncrystalline U(IV)," oxidize more rapidly than does UO 2+x (14).…”
mentioning
confidence: 99%
“…However, the long-term fate of U in wetlands remains unclear, especially when they exhibit intermittent oxidizing conditions due to water-table fluctuations [10]. Indeed, non-crystalline U species that have been identified as major U species in wetlands, such as mononuclear U(VI) and U(IV) complexes bound to organic matter [10,[11][12][13], are known to be potentially mobile under both oxic [14][15][16][17] and anoxic conditions [7,18]. In addition, U(IV)-phosphate minerals may also play an important role in U retention in mining-contaminated wetlands.…”
Section: Introductionmentioning
confidence: 99%
“…19-22 Furthermore, U(IV) can complex with NOM functional groups, resulting in the formation of monomeric U(IV) species that have been observed in anoxic sediments and ore deposits together with other crystalline U(IV) phases such as uraninite. 23-26 Other studies reported NOM complexation influences the abiotic oxidation rate of Fe(II) by O 2 . 27-29 For example, functional groups such as quinones act as terminal electron acceptors in anaerobic microbial respiration, while phenols serve as electron donors for the reduction of electron acceptors, such as Fe(III), Mn(IV), arsenate, Cr(VI), and U(VI).…”
Section: Introductionmentioning
confidence: 99%